Il concetto di alterità tra psicanalisi lacaniana e antropologia ontologica: Una prospettiva politica sulla produzione della differenza - Eid Mendes, Tássia (Scenari, 2021)
Psychoanalysis and anthropology share a common history made of confrontations and conflicts. Jacques Lacan’s work bears the marks of this prolific and difficult dialogue: in order to reform the sciences of the psyche, he incorporated some concepts taken from anthropology, but he soon criticized the discipline because of its disinterest towards the subjective dimension of the human “facts”. Many anthropologists had as well shown skepticism towards psychoanalysis’ Eurocentric approach. In this article we take into account the possibility of confronting the work of Lacan with the one of the anthropologist Eduardo Viveiros de Castro. Focusing on the methods of psychoanalytical listening and ethnological description, we try to show why these two approaches share a similar conception of otherness and a common political agenda.